The experience of palliative care among older Chinese people in nursing homes: A scoping review. (May 2021) - He, Flora Xuhua; Geng, Xiaowei; Johnson, Amanda
Abstract: Objective: To identify the gaps in understanding the experience of older Chinese people receiving palliative care in nursing homes. Design: A nine-step scoping review methodology was used to search for relevant literature. Methods: Sixteen databases were searched for relevant studies published in English from January 1990 to August 2019. The grey literature was searched for relevant theses pertaining to the topic. Results: A total of 18 studies from the United States ( n  = 2), mainland China ( n  = 1), Hong Kong ( n  = 13), Taiwan ( n  = 2) and one thesis from Hong Kong were included in the final analysis. The findings were categorised into four themes: (1) advance care planning preferences; (2) decision-making process related to palliative care; (3) palliative care experiences and barriers; and (4) practice to improve palliative care. Conclusions: Given the distinctive experiences of older Chinese residents in nursing homes when faced with death and dying, cultural beliefs strongly influenced their attitudes and behaviours in receiving end-of-life care. As Chinese immigrants have become a major ethnic group in western countries, there is benefit in recognising that older Chinese people living in nursing homes and needing palliative care will face specific challenges. Culturally appropriate interventions to address older Chinese people's existential stress, grief related to loss, communication and dietary requirements, and other barriers should be developed and implemented.